PENGARUH MOTIVASI BELAJAR DAN PERILAKU BELAJAR TERHADAP HASIL BELAJAR MATA KULIAH PENGANTAR AKUNTANSI (STUDI EMPIRIS PADA MAHASISWA PENDIDIKAN EKONOMI UR, UIN SUSKA RIAU DAN UIR ANGKATAN 2014) - ', Fahminur; ', Suarman; Trisnawati, Fenny (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine whether the motivation to learn and learning behavior affects the learning outcomes of the course Introduction to Accounting on Economic Education students of the University of Riau, UIN Suska Riau and Riau Islamic University class of 2014. The subjects were students of Economic Education University of Riau, UIN Suska Riau and Riau Islamic University class of 2014 numbered 80 people, samples were taken using Purposive Sampling method. The data used are primary data and secondary data with data collection using questionnaires and interviews. Data analysis technique used is Multiple Linear Regression Analysis were processed by SPSS 21.0 For Windows and Microsoft Excel program. The results of this study indicate that the motivation to learn and learning behavior have a significant effect on learning outcomes. Means higher learning motivation and learning behavior then it will also improve the student learning outcomes. Thus, to improve learning outcomes required motivated and learn good behavior. Keywords: Motivation, Behavior Learning, Learning Outcomes